PUBLIC EXPENDITURES EVOLUTION. POSITIVE OR NEGATIVE ASPECTS? - Mihai-Bogdan, PETRIȘOR (Strategii Manageriale)
This article analyzes the situation of public spending and the transformations that occurred in state budgets over the past ten years in Romania. Data are collected from eurostat, state budgets laws and corrections occurred. Simultaneously, there is a parallel with the evolution of public debt.